Mechanical, Elastic, and Adhesive Properties of Two‐Dimensional Materials: From Straining Techniques to State‐of‐the‐Art Local Probe Measurements. Issue 13 (4th April 2022) - Di Giorgio, Cinzia; Blundo, Elena; Pettinari, Giorgio; Felici, Marco; Bobba, Fabrizio; Polimeni, Antonio
Abstract: 2D materials, such as graphene, hexagonal boron nitride (hBN), and transition‐metal dichalcogenides (TMDs), are intrinsically flexible, can withstand very large strains (>10% lattice deformations), and their optoelectronic properties display a clear and distinctive response to an applied stress. As such, they are uniquely positioned both for the investigation of the effects of mechanical deformations on solid‐state systems and for the exploitation of these effects in innovative devices. For example, 2D materials can be easily employed to transduce nanometric mechanical deformations into, e.g., clearly detectable electrical signals, thus enabling the fabrication of high‐performance sensors; just as easily, however, external stresses can be used as a "knob" to dynamically control the properties of 2D materials, thereby leading to the realization of strain‐tuneable, fully reconfigurable devices. Here, the main methods are reviewed to induce and characterize, at the nm level, mechanical deformations in 2D materials. After presenting the latest results concerning the mechanical, elastic, and adhesive properties of these unique systems, one of their most promising applications is briefly discussed: the realization of nano‐electromechanical systems based on vibrating 2D membranes, potentially capable of operating at high frequencies (>100 MHz) and over a large dynamic range. Abstract : Atomically thin 2D materials exhibit outstanding mechanical robustness as compared to 3D crystals. This feature and the exceptional tunability of the optical and electronic properties of 2D crystals under strain has boosted the emerging fields of flextronics and straintronics. Knowledge of the adhesion and elasticity properties is thus pivotal to the manufacturing and integration of 2D crystal‐based devices.